CD22-targeted CAR T cells induce remission in B-ALL that is naive or resistant to CD19-targeted CAR immunotherapy - Fry, Terry J; Shah, Nirali N; Orentas, Rimas J; Stetler-Stevenson, Maryalice; Yuan, Constance M; Ramakrishna, Sneha; Wolters, Pamela; Martin, Staci; Delbrook, Cindy; Yates, Bonnie; Shalabi, Haneen; Fountaine, Thomas J; et al. (Nature medicine, 2018)
Chimeric antigen receptor (CAR) T cells targeting CD19 mediate potent effects in relapsed and/or refractory pre-B cell acute lymphoblastic leukemia (B-ALL), but antigen loss is a frequent cause of resistance to CD19-targeted immunotherapy. CD22 is also expressed in most cases of B-ALL and is usually retained following CD19 loss. We report results from a phase 1 trial testing a new CD22-targeted CAR (CD22-CAR) in 21 children and adults, including 17 who were previously treated with CD19-directed immunotherapy. Dose-dependent antileukemic activity was observed, with complete remission obtained in 73% (11/15) of patients receiving ≥1 × 10 CD22-CAR T cells per kg body weight, including 5 of 5 patients with CD19 or CD19 B-ALL. Median remission duration was 6 months. Relapses were associated with diminished CD22 site density that likely permitted CD22 cell escape from killing by CD22-CAR T cells. These results are the first to establish the clinical activity of a CD22-CAR in B-ALL, including leukemia resistant to anti-CD19 immunotherapy, demonstrating potency against B-ALL comparable to that of CD19-CAR at biologically active doses. Our results also highlight the critical role played by antigen density in regulating CAR function.